Pengaruh Social Influence dan Facilitating Condition Terhadap Use Behaviour Mobile Banking Mandiri di Karawang - Alfattaah, Muhammad Syahid; Fuadah, Siti Rohmatul; Situngkir, Tiar Lina (Value : Journal of Management and Business, 2024)
This research employs the UTAUT model to examine the impact of Social Influence and Facilitating Condition variables on behavior intention and Use Behavior among users of the Mandiri mobile banking application in Karawang. The purposive sampling method yielded 110 respondents, who were then subjected to path analysis using SPSS 25 to analyze the data. The Facilitating condition and social influence have a favorable and considerable impact on behavior intention. Behavior intention and facilitating condition variables have a impact on utilization behavior.